Magnitude of urban malaria and its associated risk factors in Damboya town, Kambata zone, Central Ethiopia - Biruk Mulachew; Temesgen Bezuayehu; Solomon Asnake (Parasite Epidemiology and Control)
Background: As Sub-Saharan African country urban malaria is potential catastrophe in Ethiopia, particularly in relation to rapidly growing small towns, which requires updating the epidemiology of malaria. There was lack of information regarding the study area, hence this study was designed to determine the prevalence of malaria and associated risk factors in Damboya town. Methods: A Community-based cross-sectional study was carried from March 7 to May 29, 2023 among 422 randomly selected participants. Prevalence of malaria was determined using microscopic examination of thick and thin smear and rapid diagnostic test using kits to standard of the manufacturer. Pretested structured questionnaire was employed to collect socio-demographic data and associated risk factors. Data were entered in Epi data 3.1 and analyzed using SPSS version 25 software. Factors associated with malaria was analyzed using bivariable and multivariable binary logistic regression. The strength of the association was determined by computing Adjusted Odds Ratio (AOR) at Malaria is one of the most vital leading cause of morbidity and mortality in developing countries particularly in Sub Saharan Africa (Bugssa and Tedla, 2020). About 95 % of all malaria cases and 96 % of all malaria deaths in 2021 occurred in Africa (Bugssa and Tedla, 2020). Sub-Saharan Africa accounted for 60 % of global cases and 90 % of global fatalities (WHO, 2022). Over the two peak years of the pandemic (2020–2021), COVID-related setbacks increased malaria cases by around 13 million and fatalities by 63,000 (WHO, 2022). Malaria is thought to directly cost Africa $12 billion annually and reduce GDP growth by 3 %. In addition, it is thought to cause cognitive disorders and school absences, which are barriers to the development of human capital (Monroe et al., 2022). 95 % confidence interval (CI) and p-value of <0.05. Result: The prevalence of malaria was 5 % (20, 95 % CI: 3–7), Plasmodium vivix account for 14 (61.9 %) of the infection. Presence of stagnant water (AOR = 3.630, 95 % CI: 1–13, P < 0.049), unavailability of Insecticide-treated bed net (AOR = 3.89, 95 % CI: 1.08–14.01, P < 0.038), living in a house with eaves (AOR = 5.06, 95 %CI: 1.25–20.58, p < 0.023), travel history (AOR = 3.58, 95 %CI: 1–12.79, p < 0.049), low-income (AOR = 5.3, 95 %CI: 1.09–25.2, P < 0.038), were significantly associated with malaria occurrence. Conclusion: Malaria is still a public health concern in Damboya town. Thus, implementing intervention strategies properly and evaluate the access and utilization status of the suburb community and improve accordingly was required to interrupt the transmission in the community of this town.